Effects of calcination temperature on morphological and crystallographic properties of oyster shell as biocidal agent. Issue 2 (3rd November 2020) - Park, Kitae; Sadeghi, Kambiz; Thanakkasaranee, Sarinthip; Park, Ye‐In; Park, Junsoo; Nam, Ki‐Ho; Han, Haksoo; Seo, Jongchul
Abstract: To develop biocompatible antimicrobial agent, oyster shell wastes were thermally calcined at different temperatures ranging from 300 to 1000 °C. The chemical compositions and properties of oyster shells were characterized. As such, crystallographic analysis presented that oyster shells had a hexagonal crystalline shape, and calcination process reduced their crystalline size, volume (grain dimension), and bond length, which strongly affected antimicrobial efficacy. Results showed that the main components of uncalcined and calcined oyster shells were CaCO3 and CaO, by which CaO was found to be the main antimicrobial component. Notably, calcined oyster shells showed antimicrobial potency against both Gram‐negative ( Escherichia coli) and Gram‐positive ( Staphylococcus aureus) . Furthermore, cytotoxicity analysis proved that calcined oyster shells had good cell viability and low cytotoxicity. Results highlighted that calcined oyster shells, particularly those treated at 750°C, could be a biocompatible alternative to synthetic biocidal and antimicrobial agents using in food packaging, biomedical, and cosmetic industries.